Pelaksanaan Pendidikan Agama Non Formal Dalam Pembinaan Masyarakat Islami - Aidil Saputra (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2017)
Non-formal education: education outside of school as well as outside the household whohave had certain rules, but not so tight as bound and formal education. The purposeof religious education non-formal to increase faith, understanding, appreciation andpractice of a child in an institution non-formal education about Islam so that a man true Muslim that is faithful and devoted to God, and morality in personal, social, state and nation. Non-formal religious education among them; Aqidah, Shari’ah, Worshipand Morals. Environmental non-formal education is human society, it will determine thesuccess or failure of implementation. institutions of religious education in society, amongothers: Mosque, Traditional Pesantren, pengajians Hall, Place pengajians Qur’an,PesantrenKilat, and meunasah. The responsibility of non-formal religious education,not only by a person / group only within the community but a shared responsibility asMuslims